Creating States : Studies in the Performative Language of John Milton and William Blake - Esterhammer, Angela (Book collections on Project MUSE., 1994)
Analysing texts such as The Reason of Church Government, Paradise Lost, The Marriage of Heaven and Hell, and Jerusalem, Esterhammer traces the parallel evolution of Milton and Blake from writers of political and anti-prelatical tracts to poets who, having failed in their attempts to alter historical circumstances through a direct address to their contemporaries, reaffirm their faith in individual visionary consciousness and the creative word - while continuing to use the forms of a socially or politically performative language.